Differential regulation of Treg stability in human naïve and effector Treg subsets by TGFβ-signaling via ARKADIA-SKI axis - Yang, Fan; Yanes, Alexis; Li, Miao; Heizer, Patrick; Linatoc, Ivan; Stephens, Michael E.; Song, Yang; Ort, Tatiana; Bednar, Kyle J.; Ikeda, Yasuhiro; Guo, Zengli (Frontiers in Immunology, 2025)
IntroductionThe human FOXP3+ regulatory T (Treg) cells, a subset of CD4+ T cells with immunosuppressive function, are essential for the maintenance of immune homeostasis and tolerance. Treg cells are a heterogeneous population, subdivided into a less stable “effector” subset and a more stable “naïve” subset. Under inflammatory conditions, Treg cells can lose their immunosuppressive properties, contributing to the development of autoimmune diseases. The TGFβ signaling is pivotal for the induction of Treg cells from naïve CD4 T cells and the thymic development of natural Treg cells. However, how TGFβ signaling regulates established naïve and effector Treg cells is not fully understood.MethodsHuman naïve and effector Treg cells were isolated from healthy donors using flow cytometry. Different subsets of Treg cells were treated with a TGFβ inhibitor or genetically modified to express SKI or ARKADIA via lentiviral transduction. Treg cell phenotype, stability and signaling regulation were analyzed using flow cytometry, western blotting, transcriptomic and meta-analyses. The functionality of Treg cells was analyzed by in vitro coculture assays.ResultsWe find that the TGFβ signaling is differentially regulated in Treg subsets, with higher activity in the naïve Treg subset. Blockade of TGFβ pathway destabilizes both naïve and effector Treg cells, disrupting their immunosuppressive functions, with effector Treg cells being more susceptible. Further analysis shows that naïve Treg cells express lower levels of SKI protein, a negative regulator of TGFβ signaling suppressed by TGFβ-induced protein degradation. SKI overexpression destabilizes Treg cells and disrupts their immune suppressive function. Transcriptomic and meta-analyses reveal that TGFβ blockade and SKI overexpression commonly modulate pathways crucial for Treg to effector T cell conversion, downregulating Treg signature genes and upregulating effector T cell markers, which are validated as potential SKI targets. Importantly, overexpression of ARKADIA, an E3 ubiquitin ligase of SKI, efficiently reduces SKI levels, enhancing Treg cell stability and functionality under both TGFβ inhibition and chronic proinflammatory cytokine stimulation.ConclusionOur results identify a previously unrecognized role of the TGFβ-ARKADIA-SKI axis in regulating the stability and functionality of human Treg subsets, highlighting novel strategies for harnessing TGFβ-associated pathways to stabilize human Treg cells for clinical applications.